Visual Exposure to Natural Environments Decreases Delay Discounting of Improved Air Quality - Berry, Meredith S.; Repke, Meredith A.; Conway, Lucian G. (Frontiers in Public Health, 2019)
Poor air quality contributes to nearly 7 million premature deaths annually and remains a major public health concern. In order to directly address the future of air quality and current emissions, some economists and policy makers have stressed adopting a 'zero discount rate' (or lowest possible) to promote clean air quality now and in the future. A low discount rate is also associated with individual health behaviors (e.g., exercise, lower rate of substance abuse). But what influences the psychology of decision-making that is relevant to the discount rate of air quality and public health outcomes, and individual health? The present experiments evaluated differences in such decision-making (i.e., delay-discounting) in the context of improved air quality with visual exposure to natural versus built environments. Results showed that individuals exposed to natural scenes discounted improved air quality less (i.e., made more future-oriented decisions, Experiment 1), and this may be related to expanded space perception (Experiment 2). These results are the first to suggest that delay discounting of air quality (or any environmental outcome), similar to money, is malleable, and can be influenced by exposure to natural relative to built environments. These findings have implications for influencing long-term, individual health and environmentally relevant decision-making and improving individual and public health related outcomes such as air quality.